Ngah Ibrahim in Larut 1858 - 1874 - Wee, Choon Siang ([Singapore : s.n., 1952)
This microfilm is mainly based on official documents, of which the Straits Settlements Records from the major part for the period before 1867.
Keywords: Ngah Ibrahim, -- 1840-1895; British -- Malaysia -- Perak -- History; Perak -- History